Teacher's Efforts to Improve Symbolic Thinking Ability Through Jampit (Clock Clock) Media for Group B Children in Ra Teladan Imam Syafi'i Academic Year 2023/2024 - Santini, Saskia Aulia; Rahayu, Eka Pamuji; Eliyana, Eliyana (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study aims to improve children's symbolic thinking abilities through the use of clothespins as a media tool in group B children at RA Teladan Imam Syafi'i. This study is classroom action research (CAR) consisting of four stages: the first stage is the planning stage, the second stage is the implementation stage, the third stage is observation, and the fourth stage is reflection. The subjects of this study were 20 children in group B aged 5-6 years, consisting of 13 boys and 7 girls. Data were collected using data collection techniques such as observation, interviews, and documentation. The data analysis technique involved calculating the number of children achieving class mastery and individual mastery. The results of this study indicate that using clothespins as a media tool in group B children at RA Teladan Imam Syafi'i improves children's symbolic thinking abilities. Data show an improvement in children's abilities from before the intervention to the implementation of cycle II. The data before the intervention showed an initial percentage of 25%. After implementing the classroom action in cycle I using clothespins, the researcher obtained a percentage increase to 50%. In cycle II, the research achieved an 80% increase in the criteria of Developing as Expected (BSH).